1989
DOI: 10.1177/109019818901600210
|View full text |Cite
|
Sign up to set email alerts
|

The Stanford Adolescent Heart Health Program

Abstract: This study was designed to create, implement, and test a school-based multiple risk factor reduction program for high school students. All tenth graders in four senior high schools (N = 1447) from two school districts participated in the study. Within each district, one school was assigned at random to receive a special 20-session CVD risk reduction intervention and one school served as a control. The schools were matched for size and distribution of racial groups before randomization. At a two-month follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Students in the intervention schools reported significant knowledge gains and increases in regular exercise. 50,54 Positive treatment effects also were observed for BMI, skinfolds, and resting heart rate. LEAP was a comprehensive physical activity intervention designed to change the instructional program and school environment to increase support of physical activity for ninth-grade girls.…”
Section: Evidence: Physical Activity During the School Day And Withinmentioning
confidence: 74%
“…Students in the intervention schools reported significant knowledge gains and increases in regular exercise. 50,54 Positive treatment effects also were observed for BMI, skinfolds, and resting heart rate. LEAP was a comprehensive physical activity intervention designed to change the instructional program and school environment to increase support of physical activity for ninth-grade girls.…”
Section: Evidence: Physical Activity During the School Day And Withinmentioning
confidence: 74%
“…Twelve of these studies had positive effects on students' health-related fitness knowledge, six studies had a positive effect on students' physical activity levels, and five studies significantly influenced students' fitness levels. Seven of these 12 studies revealed intervention effects both on health-related fitness knowledge and on physical activity (four studies: Harrell et al, 1996;Killen et al, 1989;Manios & Kafatos, 1999;Marcus, Channing Wheeler, Cullen, & Crane, 1987) or fitness levels (three studies: Bush, Zuckerman, Taggart, et al, 1989;Fardy, White, Haltiwanger-Schmitz, & Magel, 1996;Perry et al, 2002). Finally, the results concerning the one study by Caballero et al (2003) with a high methodological quality are unclear because on the one hand, positive effects on students' physical activity were revealed from the data assessed by questionnaire and on the other hand, no intervention effects were shown from the data assessed by a physical activity motion sensor.…”
Section: Y Demetriou Et Al / Educational Research Review 16 (2015) mentioning
confidence: 96%
“…Most comprehensive community-based interventions have focused on cardiovascular disease risk reduction [274,275]. Successful obesity interventions are contingent on targeting multiple aspects of children's environments [276].…”
Section: Large-scale Community/environmental Interventionsmentioning
confidence: 99%